Low androgen signaling rescues genome integrity with innate immune response by reducing fertility in humans - J. Zimmer; L. Mueller; P. Frank-Herrmann; J. Rehnitz; J. E. Dietrich; M. Bettendorf; T. Strowitzki; M. Krivega (Cell Death and Disease, 2024)
Abstract Development of the gonads under complex androgen regulation is critical for germ cells specification. In this work we addressed the relationship between androgens and genomic integrity determining human fertility. We used different study groups: individuals with Differences of Sex Development (DSD), including Complete Androgen Insensitivity Syndrome (CAIS) due to mutated androgen receptor (AR), and men with idiopathic nonobstructive azoospermia. Both showed genome integrity status influenced by androgen signaling via innate immune response activation in blood and gonads. Whole proteome analysis connected low AR to interleukin-specific gene expression, while compromised genome stability and tumorigenesis were also supported by interferons. AR expression was associated with predominant DNA damage phenotype, that eliminated AR-positive Sertoli cells as the degeneration of gonads increased. Low AR contributed to resistance from the inhibition of DNA repair in primary leukocytes. Downregulation of androgen promoted apoptosis and specific innate immune response with higher susceptibility in cells carrying genomic instability.